Hindu Conception of the Deity as Cqlminating in. Ramanuja, - Chandrankunnel, Mathew (Journal of Dharma, 1980)
Bharatan Kurmarappa, The Hindu Conception of the Deity as Culminating in Ramanuja, " Delhi : Inter Indi Publications, Reprint, 1979, First ed. 1934, pp. 356,’ Rs. 80 ( 16).